Mutuality without alliance: the roles of community in becoming a college student feminist. Issue 7 (3rd October 2019) - Marine, Susan; Lewis, Ruth
ABSTRACT: Feminism has made a resurgence in the last several years, especially on college campuses [Davies. 2011. "Feminism is back, and we want to finish the revolution, say activists." The Guardian, August 5. https://www.theguardian.com/world/2011/aug/05/feminism-resurgent-activists ]. Actions to address sexual violence and other forms of 'lad culture' are growing in visibility, as young feminists come together to challenge patriarchal norms on campuses. Little is known about how feminist community functions to solidify individuals' commitment to liberatory action. The meaning-making process of college-age feminists in the US/UK is relevant to the ongoing question of how social change movements function and flourish. This study chronicled 33 college feminists in the US and UK, describing how feminist communities on campus served to foster stronger commitment to feminism and greater confidence in advocating for feminist values and viewpoints. Community forged through consciousness of one's differential power and privilege and productive engagement with identity difference was notably absent in these narratives, signaling incomplete encounters with cross-coalitional alliance [Rowe. 2008. Power Lines. On the Subject of Feminist Alliances . Durham: Duke University Press].